EFFECTS OF THE LASER AND ITS APPLICATION IN ORAL SURGERY - Gjorovska, Maja Popovska; Kacarska, Marina (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
The rapid advancement of technology enables the invention of highly sophisticated  light scalpel lasers with the use of which in oral surgery has achieved better results. It was a challenge and     a purpose to emphasize the effects and advantages of laser surgery unlike the conventional scalpel technique. The wider application of the laser in dentistry is due to the effects of the laser beam on organic tissue.   1.Photo-stimulating effect - restoring the cell's function to its normal and stimulating its activity.   2.Photo-thermal effect - the laser energy in contact with tissue transforms into thermal energy and causes coagulation of the blood vessels, thus providing a dry working field.   Photomechanical effect - ablative effect, vaporization (evaporation of water from tissues), i.e. cutting and remodeling the soft tissue.   4.Photodynamic effect-is used to remove tumor cells sensitized by chromophore. After               intravenously administering haemoporphyrin, which cleans healthy cells of chromophore for 1-2 days, while in tumor cells, it is retained for 12 days. The laser is absorbed in the chromophore and destroys the marked cells.   The effects of the laser beam, the positive experiences from its application confirmed by scientific evidence are challenging a large number of surgical indications in dentistry to be treated with its application. At the Clinic for Ð¾ral surgery the following clinical cases were treated: removal of the labial frenulum, hyperplasia of the mucous membrane (epulis fissuratum), deepening of the vestibular fornix, gingivectomy and chemical scar.   Key words: laser, labial frenulum, frenulectomy, fibrous hyperplasia, gingivectomy, chemical scar.